2014
DOI: 10.11634/216796061403551
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Role of Career Development Programs in Organizations and Organizational Commitment on Job Satisfaction of Employees

Abstract: In this study; the impact of career development programs in organizations, and organizational commitment on employees' job satisfaction, and their role in increasing job satisfaction are examined. A survey is applied in a sample group working in various industries. At this point, a questionnaire that consists of two sections of 43 questions rated on a 7-point Likert attitude scale is prepared. The survey was conducted on 204 employees that work in different sectors. In the study, the data obtained from the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 6 publications
1
25
0
2
Order By: Relevance
“…Even if the results reported an insignificant relationship between EDP and organizational commitment but when mediated by job satisfaction the relationship became significant (see Table ). This can be attributed to the fact that skill development need not always result in increased commitment, since, commitment is more closely related to job satisfaction (Kaya & Ceylan, ). EDP sharpens professional skills of the employees but may fail in nurturing a personal bond, which is a pre‐requisite for commitment (Fiorito et al ., ).…”
Section: Resultssupporting
confidence: 92%
“…Even if the results reported an insignificant relationship between EDP and organizational commitment but when mediated by job satisfaction the relationship became significant (see Table ). This can be attributed to the fact that skill development need not always result in increased commitment, since, commitment is more closely related to job satisfaction (Kaya & Ceylan, ). EDP sharpens professional skills of the employees but may fail in nurturing a personal bond, which is a pre‐requisite for commitment (Fiorito et al ., ).…”
Section: Resultssupporting
confidence: 92%
“…Future researcher can do work to the remaining related aspects such as career performance, job stress, trust, and ethics. (Kaya & Ceylan, 2014) Examined the Career development initiatives in companies and corporate contribution to job satisfaction for workers are analyzed, and their role in that job satisfaction. A survey is conducted within a sample group that works in different industries.…”
Section: Individualism (Dimension Of Culture Hofstede)mentioning
confidence: 99%
“…Coetzee & Potgieter (2014) found that career management at the organization and individual levels are positively influenced employees self-esteem. Kaya & Ceylan (2014) findings indicated that career path management lead to organizational commitment, and employees' satisfaction at Istanbul province in Turkey. Shawabkeh (2017) indicated that there is a positive influence of career path management and planning on creating citizenship behavior of the middle level managers at Greater Amman Municipality.…”
Section: Benefits Of Career Path Managementmentioning
confidence: 89%